INCREASING CALCIUM CARBONATE (CaCO3) TO GROWT AND SURVIVAL RATE VANNAMEI SHRIMP (Litopenaeus vannamei)) - Unggul Fitrah Heriadi; Mulyadi '; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in March 2016 - April 2016 for 21 days at the NationalBroodstock Center For Shrimp and Mollusk Karangasem Bali. The purpose of this study todetermine the effect of calcium carbonate (CaCO3) on the growth and survival rate vanameishrimp (Litopeneaus vannamei). Vanamei shrimp size PL25 were used in the research. Thecontainer used fiber tub with capacity 250 liters and the volume of water used is 100 liters.The treatment is giving of calcium carbonate 20 mg, 35mg, 50mg, 65mg and 80mg and addedthe control treatment. This research uses a completely randomized design (CRD), level 6treatments and 3 replications. The results showed that the best treatment contained in P4 withthe addition of calcium carbonate as much the amount of shrimp molting 408 times. theabsolute length of 2.26 cm in the growth of absolute weight of 1.47 grams, daily growth rateof 2.29% and 87.7% survival rate as 65 mg/L,Keywords: Calcium Carbonate, Vannamei shrimp, moulting, survival rate